PENGARUH UMUR BATANG BAWAH DAN NAUNGAN TERHADAP PERTUMBUHAN SAMBUNG DINI DURIAN (Durio zhibertinus L.) - Rama Robbi Ghifari; Susiyanti; Julio Eiffelt Rossaffelt Rumbiak; Alfu Laila (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine the effect of rootstock age and shade on early grafting growth of durian (Durio zibethinus L.). The environmental design used in this study was using a Split Plot with the main plot being the effect of shading and the subplot being the age of the rootstock which was replicated 3 times. The treatment design consisted of a main plot and subplots. The main plot is the effect of shading (N) with 3 different light intensity levels : N1: 40% light intensity N2: 60% light intensity N3: 80% light intensity. Subplots were the effect of rootstock age (U) which consisted of 3 levels, namely: U1: Age of rootstock 2 weeks. U2 : Age of rootstock 4 weeks. U3 : Age of rootstock 6 weeks. The results showed that the 4-week rootstock age treatment had the best effect on the parameters of the number of open leaves, leaf greenness index; increase in scion diameter at 1-8 (week after grafting/WAG), and increase in rootstock diameter at 8 MSP; Shading treatment of 60% had the best effect on the parameters of shoot rupture age, number of open leaves, leaf greenness index, shoot length increase at 4-8 WAG; The best interactions occurred at 60% shade treatment and 6 weeks of rootstock age on the parameters of bud break age and leaf greenness index; Shade treatment 60% and rootstock age 8 weeks on parameters Number of open leaves, and increase in shoot length; Shade treatment of 80% and rootstock age of 8 weeks for the parameters of scion diameter increase; and 40% shading treatment and rootstock age of 6 weeks for the parameter of rootstock diameter increase.